The Menace of Moral Degenerations in Nigeria’s Tertiary Institutions: Islamic Universities to the Rescue - Suraju, Saheed Badmus (Jurnal Ilmiah Peuradeun, 2019)
It is not an overstatement to say that things continue to degenerate everyday in all aspects of human life, especially the social aspect. This social life of man is full of transgression and corruption which have led to moral degeneration in the society. These societal evils have extended their tentacles to educational life of man, the Tertiary Institutions in Nigeria especially the Universities, which are to provide the needed man power, acquisition of skills and refinement of moral for the future leaders of the country, have become the breeding grounds for ignoramus, hoodlums, cheaters, rapists, prostitutes, etc. The study adopted historical, descriptive and phenomenological methods in carrying out the research. The paper revealed some notable immoralities which are the order of the day in the Nigerian Tertiary Institutions and are posing threats to educational developments in the nation. The paper concluded that religious universities are alternatives in controlling the rate at which the immoralities are growing. Thus, it recommended that Islamic Universities should be given licenses as the lasting solution to the menace through their series of programmer which are in consonance with the tenets of Islam.